2006
DOI: 10.1530/rep.1.01186
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endocrine profile and reproductive organs during puberty in the male marmoset monkey (Callithrix jacchus)

Abstract: Data on pubertal maturation in male marmoset, a model for human reproduction, are scant and conflicting. We collected data on novel parameters to characterize puberty. Twenty-five marmoset monkeys were assigned to five age groups by weeks (wk): 21 (pre-pubertal), 43 (onset of puberty), 52 (fully pubertal), 70 (mature), and 116 (fully adult). Serum and intratesticular testosterone and pituitary bioactive chorionic gonadotropin (bioCG) were measured. Testicular development was assessed by ultrasonography, histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
(38 reference statements)
1
45
1
Order By: Relevance
“…While reduced testicular volume was found, the serum testosterone levels remained in the physiological range typical of adult animals (see Chandolia et al (2006)) and the histological evaluation of testicular tissue showed mild effects of reduced spermatogenesis and rarely mixed atrophy. In order to establish the suppressive effects of NETE only and -indirectly -the impact of exogenous testosterone spermatogenesis in Callithrix jacchus -either after initial co-administration with TU or by direct use of NETE only -we added the two treatment groups in which, after TU/NETE administration, NETE only was administered (extended gestagen effect, regimen II) and one group that received NETE only (regimen III).…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 96%
See 3 more Smart Citations
“…While reduced testicular volume was found, the serum testosterone levels remained in the physiological range typical of adult animals (see Chandolia et al (2006)) and the histological evaluation of testicular tissue showed mild effects of reduced spermatogenesis and rarely mixed atrophy. In order to establish the suppressive effects of NETE only and -indirectly -the impact of exogenous testosterone spermatogenesis in Callithrix jacchus -either after initial co-administration with TU or by direct use of NETE only -we added the two treatment groups in which, after TU/NETE administration, NETE only was administered (extended gestagen effect, regimen II) and one group that received NETE only (regimen III).…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 96%
“…ITT and serum testosterone were determined as described by Chandolia et al (1991Chandolia et al ( , 2006. For ITT, frozen testicular tissue samples were homogenized in 250 ml PBS buffer and dissolved by ultrasound.…”
Section: Hormone Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of culturing time, medium was collected and measured for testosterone levels using an in-house RIA (Zamecnik et al, 1977;Chandolia et al, 2006), and cells were collected for RNA extraction. Experiments were performed with three independent cultures.…”
Section: Cell Culturementioning
confidence: 99%